Positive vasoreactivity testing in pulmonary arterial hypertension: therapeutic consequences, treatment patterns, and outcomes in the modern management era - Gerhardt, Felix; Fiessler, Eva Marie; Olsson, Karen M.; Kayser, Moritz Z.; Kovacs, Gabor; Gall, Henning; Ghofrani, H. Ardeschir; Badr Eslam, Roza; Lang, Irene M.; Benjamin, Nicola; Grünig, Ekkehard; Halank, Michael; et al. (Circulation, 2024)
BACKGROUND: - Among patients with pulmonary arterial hypertension (PAH), acute vasoreactivity testing during right heart catheterization may identify acute vasoresponders, for whom treatment with high-dose calcium channel blockers (CCBs) is recommended. However, long-term outcomes in the current era remain largely unknown. We sought to evaluate the implications of acute vasoreactivity response for long-term response to CCBs and other outcomes. - METHODS: - Patients diagnosed with PAH between January 1999 and December 2018 at 15 pulmonary hypertension centers were included and analyzed retrospectively. In accordance with current guidelines, acute vasoreactivity response was defined by a decrease of mean pulmonary artery pressure by ≥10 mm Hg to reach <40 mm Hg, without a decrease in cardiac output. Long-term response to CCBs was defined as alive with unchanged initial CCB therapy with or without other initial PAH therapy and World Health Organization functional class I/II and/or low European Society of Cardiology/European Respiratory Society risk status at 12 months after initiation of CCBs. Patients were followed for up to 5 years; clinical measures, outcome, and subsequent treatment patterns were captured. - RESULTS: - Of 3702 patients undergoing right heart catheterization for PAH diagnosis, 2051 had idiopathic, heritable, or drug-induced PAH, of whom 1904 (92.8%) underwent acute vasoreactivity testing. A total of 162 patients fulfilled acute vasoreactivity response criteria and received an initial CCB alone (n=123) or in combination with another PAH therapy (n=39). The median follow-up time was 60.0 months (interquartile range, 30.8-60.0), during which overall survival was 86.7%. At 12 months, 53.2% remained on CCB monotherapy, 14.7% on initial CCB plus another initial PAH therapy, and the remaining patients had the CCB withdrawn and/or PAH therapy added. CCB long-term response was found in 54.3% of patients. Five-year survival was 98.5% in long-term responders versus 73.0% in nonresponders. In addition to established vasodilator responder criteria, pulmonary artery compliance at acute vasoreactivity testing, low risk status and NT-proBNP (N-terminal pro-B-type natriuretic peptide) levels at early follow-up correlated with long-term response and predicted survival. - CONCLUSIONS: - Our data display heterogeneity within the group of vasoresponders, with a large subset failing to show a sustained satisfactory clinical response to CCBs. This highlights the necessity for comprehensive reassessment during early follow-up. The use of pulmonary artery compliance in addition to current measures may better identify those likely to have a good long-term response.
Gesehen am 18.02.2025
Originalveröffentlichung: 12. April 2024